Magnetic Phase Diagram of Cu4–xZnx(OH)6FBr Studied by Neutron-Diffraction and μSR TechniquesSupported by the National Key Research and Development Program of China (Grant Nos. 2017YFA0302900, 2016YFA0300500, 2018YFA0704200, 2017YFA0303100, and 2016YFA0300600), the National Natural Science Foundation of China (Grant Nos. 11874401, 11674406, 11674372, 11961160699, 11774399, 12061130200, 11974392, and 11822411), the Strategic Priority Research Program(B) of the Chinese Academy of Sciences (Grant Nos. XDB25000000, XDB07020000, XDB33000000, and XDB28000000), the Beijing Natural Science Foundation (Grant Nos. Z180008 and JQ19002), Guangdong Introducing Innovative and Entrepreneurial Teams (Grant No. 2017ZT07C062), the Youth Innovation Promotion Association of CAS (Grant No. 2016004), and the Royal Society-Newton Advanced Fellowship (Grant No. NAF\BR1\B201248). (October 2020) - Wei 魏, Yuan 源; Ma 马, Xiaoyan 肖燕; Feng 冯, Zili 子力; Adroja, Devashibhai; Hillier, Adrian; Biswas, Pabitra; Senyshyn, Anatoliy; Hoser, Andreas; Mei 梅, Jia-Wei 佳伟; Meng 孟, Zi Yang 子杨; Luo 罗, Huiqian 会仟; Shi 石, Youguo 友国; et al.
Abstract : We systematically investigate the magnetic properties of Cu4 – x Zn x (OH)6 FBr using the neutron diffraction and muon spin rotation and relaxation ( μ SR) techniques. Neutron-diffraction measurements suggest that the long-range magnetic order and the orthorhombic nuclear structure in the x = 0 sample can persist up to x = 0.23 and 0.43, respectively. The temperature dependence of the zero-field μ SR spectra provides two characteristic temperatures, T A 0 and Tλ, which are associated with the initial drop close to zero time and the long-time exponential decay of the muon relaxation, respectively. Comparison between T A 0 and T M from previously reported magnetic-susceptibility measurements suggest that the former comes from the short-range interlayer-spin clusters that persist up to x = 0.82. On the other hand, the doping level where Tλ becomes zero is about 0.66, which is much higher than threshold of the long-range order, i.e., ∼0.4. Our results suggest that the change in the nuclear structure may alter the spin dynamics of the kagome layers and a gapped quantum-spin-liquid state may exist above x = 0.66 with the perfect kagome planes.